Biological restorations: an underrated modality of pediatric restorative dentistry - Kansal, Vedant; Rana, Vivek; Srivastava, Nikhil; Kaushik, Noopur (International Journal Of Community Medicine And Public Health, 2022)
Early childhood caries (ECC) is an infectious disease of the primary teeth in children which leads to severe destruction of the teeth and results in damage to their permanent successors if not treated promptly and efficiently. Untreated carious primary teeth not only cause pain and difficulty in chewing but also lead to functional disharmony, development of deleterious habit and can affect the permanent tooth buds. Satisfactory restoration of these teeth, improving esthetics, along with the management of space and function has always been a challenge for pediatric dentist. In an attempt to widen as biologically and conservatively as possible, several authors have suggested the use of tooth fragments or extracted human teeth called as biological restorations as a restorative material to rehabilitate severely destroyed teeth. This technique allows the preservation of sound tooth structure and provides excellent aesthetics and comparable wear resistance with opposing tooth. This paper aims to review the evolution, methods and uses of these biological restorations in pediatric dentistry.